On certain properties of Î± -continuous functions - J. Mustafa, Hadi; Kh. Al- Awadi, Heyam (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this work , we introduce and study a new type of continuous functions, which we call Î±- continuous function , these are the functions in which the inverse image of Î±- open set is also Î±- open. Several properties of these functions are proved.